Numerical calculation of mass transfer from elliptical pools in uniform flow using the boundary element method - Fyrillas, Marios M.; Kontoghiorghes, Erricos John (My University, 2004)
The three-dimensional problem of advection-dispersion associated with an elliptical non-aqueous-phase liquid (NAPL) pool is addressed using the boundary element method. The boundary condition on the plane of the pool is such that over the pool the concentration is equal to the saturation concentration while a no flux boundary condition is imposed in the region not covered by the pool. The numerical results are verified by asymptotic analytical solutions obtained in the limits of diffusion-dominated and convection-dominated mass transport. For cases of practical interest an empirical expression is obtained for the Sherwood number that matches the numerical results over a wide range of the relevant parameters. Comparison with experimental results suggests that the corresponding numerical results predict a higher overall mass transfer coefficient.
Keywords: Boundary element methods; Diffusion; Mass transfer; Parameter estimation